The Crime Of Incest In Islamic Jurisprudence And The Algerian Penal Code (مجلة الواحات للبحوث والدراسات, 2026)
The article explores the crime of incest in both Islamic Jurisprudence and the Algerian Penal Code, highlighting it as one of the gravest threats to family cohesion and social values. While marriage in Islam was ordained to preserve lineage and build families, weak religious commitment and moral decline have contributed to the spread of incest. The study questions the adequacy of existing legal texts in preventing this crime, defining incest as consensual sexual relations between relatives prohibited from marriage. Its main causes include weak faith, exposure to pornography, drug abuse, and poor upbringing. Article 337 bis of the Algerian Penal Code establishes varying penalties depending on kinship, with harsher punishments for closer relations and the possibility of withdrawing parental authority. In Islamic law, incest is regarded as even more heinous than adultery, with punishments ranging from flogging and exile to stoning or even execution according to some jurists. The article concludes that effective prevention requires not only legal deterrence but also strong religious and moral education to protect the family and society.